2022
DOI: 10.3389/fcimb.2021.736506
|View full text |Cite
|
Sign up to set email alerts
|

Senecavirus A- and Non-Infected Cells at Early Stage of Infection: Comparative Metabolomic Profiles

Abstract: Senecavirus A (SVA), classified into the genus Senecavirus in the family Picornaviridae, causes an infectious disease in pigs. This virus can efficiently replicate in some non-pig-derived cells, such as the BHK cell line and its derivative (BSR-T7/5 cell line). We had recovered a wild-type SVA from its cDNA clone previously, and then uncovered the proteomic profile of SVA-infected BSR-T7/5 cells at 12 h post inoculation (hpi). In order to explore the cellular metabolomics further, the SVA-inoculated BSR-T7/5 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 55 publications
1
20
0
Order By: Relevance
“…Some viruses, such as H1N1 influenza virus and MDV, have been reported to induce host glycolysis [ 16 , 37 ]. A recently reported bioinformatics analysis of metabolism in SVA infection showed that the virus can reprogram cellular glucose metabolism [ 38 ], in agreement with the experimental results presented here. CH-GDFS-2018 is a wild type virus isolated by our group in 2018 with recombinant features [ 39 ].…”
Section: Discussionsupporting
confidence: 91%
“…Some viruses, such as H1N1 influenza virus and MDV, have been reported to induce host glycolysis [ 16 , 37 ]. A recently reported bioinformatics analysis of metabolism in SVA infection showed that the virus can reprogram cellular glucose metabolism [ 38 ], in agreement with the experimental results presented here. CH-GDFS-2018 is a wild type virus isolated by our group in 2018 with recombinant features [ 39 ].…”
Section: Discussionsupporting
confidence: 91%
“…Viruses are the most abundant and widely distributed biological entities worldwide, with varied genetic material and the ability to infect different species [ 29 ]. Furthermore, their lives depend on their host’s metabolism, including virion uncoating, genome replication, and progeny packaging [ 9 ]. The main purpose of the host’s metabolism is to convert nutrients into energy to sustain all cellular processes and provide raw materials for the biosynthesis of proteins, lipids, and nucleic acids.…”
Section: Discussionmentioning
confidence: 99%
“…Amino acids are crucial for living organisms. Many metabolomic studies have identified metabolic changes in amino acids caused by viral infections [ 9 , 40 , 41 ]. For example, murine norovirus controls the antiviral response by activating metabolic stress responses, which activate amino acid responses and impair inflammatory signaling [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Six biological replicate samples were harvested for the metabolomics analysis. The metabolites were extracted as previously described (Liu et al, 2021). In brief, the samples were lysed with pre-cooled extraction buffer (methanol:acetonitrile:water, 2:2:1, v/v/v).…”
Section: Extraction Of Metabolomics Samplesmentioning
confidence: 99%